2021
DOI: 10.1111/ene.14895
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant of the long noncoding RNA AL110200 is associated with the risk of ischaemic stroke recurrence

Abstract: Background and purpose: This study aimed to test the hypothesis that long noncoding RNA (lncRNA) AL110200 exerts a proinflammatory effect on atherosclerosis and that the variant rs901681 contributes to ischaemic stroke incidence and recurrence. Methods:The expression of AL110200 was analyzed in THP-1 cells treated with oxidized low-density lipoprotein and in human peripheral blood in a coronary heart disease and control population to determine the role of AL110200 in atherosclerosis. The effect of AL110200 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…NDM were divided into 5 quintiles, and multivariate regression analysis was conducted between NDM (quintile), Babinski sign+, pneumonia, cardiac disease and poor outcomes of AIS. The first grade of NDM (quintile) was < = 1.82, The second grade NDM (quintile) (1) was 1.83-2.41, The third grade NDM (quintile) (2) was 2.42-3.27, The fourth grade NDM (quintile) (3) was 3.28-4.49, The fifth grade NDM (quintile) (4) was 4.95+. The first grade of NDM (quintile) was the categorical covariable.…”
Section: Ndm (Quintile) Combined With Pneumonia May Better Predict Sh...mentioning
confidence: 99%
See 1 more Smart Citation
“…NDM were divided into 5 quintiles, and multivariate regression analysis was conducted between NDM (quintile), Babinski sign+, pneumonia, cardiac disease and poor outcomes of AIS. The first grade of NDM (quintile) was < = 1.82, The second grade NDM (quintile) (1) was 1.83-2.41, The third grade NDM (quintile) (2) was 2.42-3.27, The fourth grade NDM (quintile) (3) was 3.28-4.49, The fifth grade NDM (quintile) (4) was 4.95+. The first grade of NDM (quintile) was the categorical covariable.…”
Section: Ndm (Quintile) Combined With Pneumonia May Better Predict Sh...mentioning
confidence: 99%
“…Acute ischemic stroke (AIS) is a disease with high morbidity and mortality, causes considerable disability-adjusted life-years worldwide [1,2]. More seriously, numerous AIS patients have poor short-term outcomes after the onset of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a set of non-protein-coding transcripts greater than 200 bases in length [ 12 ], and are involved in a series of physiological and pathological processes, including cell differentiation, embryonic development and regulation of the cell cycle [ 13 ]. A number of lncRNAs have been reported to have diagnostic and therapeutic values in ischemic stroke [ 14 16 ]. Our previous study showed differential expression of lncRNAs in peripheral blood mononuclear cells (PBMCs) in acute ischemic stroke, revealing that a panel of altered lncRNAs (linc-DHFRL1-4, SNHG15, and linc-FAM98A-3) may serve as a novel diagnostic tool [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the existing literature shows that a number of genes may increase risk of mortality due to IS, including SERPINE1 (serine protein inhibitor E1) or plasminogen activator inhibitor 1 (PAI-1), ITGB3 (integrin beta-3), MPG (DNA-3-methyladenine glycosylase), PROCR gene (soluble endothelial protein C receptor), HABP2 (Hyaluronan Binding Protein 2), COL3A1 (type III collagen), FBG, RETN (resistin), VKORC1 (Vitamin K epoxide reductase complex subunit 1), INADL (InaD-Like Protein, PALS1-Associated Tight Junction Protein), and FXIIIA Val34Leu genetic variant [30][31][32][33][34][35][36][37][38][39][40] Moreover, the micro-RNA (miR)-10a rs3809783 A>T (MIR10A) and miR-34b/c rs4938723 T>C genetic variant (MIR34B) and the long noncoding RNA (lncRNA) AL110200 are associated with increased mortality rates due to IS [41,42].…”
Section: Introductionmentioning
confidence: 99%